2017
DOI: 10.14256/jce.1866.2016
|View full text |Cite
|
Sign up to set email alerts
|

Development of a project management performance enhancement model by analysing risks, changes, and limitations

Abstract: Development of a project management performance enhancement model by analysing risks, changes, and constraintsResults obtained by studying project performance and project management success rates are presented in the paper. The current context of construction project management practices applied in the Republic of Croatia, with principal challenges and factors influencing project management success in practical settings, is explained. A detailed comparative analysis of worldwide research focusing on project pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Researchers often use project success and project management success as similar concepts (Munns and Bjeirmi, 1996). Project management success and project success, are different notions, albeit interconnected (Radujkovic and Sjekavica, 2017). When project management is applied, project managers try to control cost, time, and progress, however, when assessing project success other criteria are used (Baccarini, 1999;Munns and Bjeirmi, 1996).…”
Section: Project Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers often use project success and project management success as similar concepts (Munns and Bjeirmi, 1996). Project management success and project success, are different notions, albeit interconnected (Radujkovic and Sjekavica, 2017). When project management is applied, project managers try to control cost, time, and progress, however, when assessing project success other criteria are used (Baccarini, 1999;Munns and Bjeirmi, 1996).…”
Section: Project Successmentioning
confidence: 99%
“…Even if project managers have not reached their goals set from a project management perspective, a project might still be regarded as successful (Munns and Bjeirmi,1996). For stakeholders, the process of finishing the project within time, scope, and budget, is key to project management, while a project can be defined as an activity taken by an enterprize to gain benefit in the longterm (Munns and Bjeirmi, 1996;Radujkovic and Sjekavica, 2017). Numerous factors can influence project success, many of which are outside the project manager's control (Munns and Bjeirmi, 1996).…”
Section: Project Successmentioning
confidence: 99%
“…Gudien ė et al [28] Factors influencing a construction project's success: external factors, institutional factors, project-related factors, PM-/team member-related factors, project-manager-related factors, client-related factors, and contractor-related factors Radujkovič and Sjekavica [29] Competent project manager (PJM), a competent team, good coordination between the manager and the team, an adequate organisational structure, culture, atmosphere, and competence, as well as a high usage of PM methodologies, methods, tools, and techniques Radujkovič and Sjekavica [30] Continuous development of competencies and improvement of management methodologies Greenwood and Miller [31] The organisational components of management activities have to include meeting the initially set deadlines and costs, making more efficient use of resources, adopting an appropriate management style, facilitating communication among the participants, and ensuring stakeholder satisfaction, with a particular focus on the project owner Ingle and Mahesh [32] Customer relations, safety, schedule, cost, quality, productivity, finance, communication and collaboration, environment, and stakeholder satisfaction.…”
Section: Causes Of Pm Implementation Methodologies Successmentioning
confidence: 99%
“…An important aspect of the construction industry is the implementation of PM success methods. The authors of [28][29][30][31][32] in their research identified factors that influence a construction project's success. A summary of studies that analyse the causes of delays in construction projects, approaches to decrease the likelihood of delays in construction, and the success of PM implementation methodologies is presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the selected factors emphasise the importance of the project manager in the construction industry [75]. Thus, within the scope of project management activities, the project manager must continuously evaluate and synchronise the management approaches with which he controls project execution [76].…”
Section: Influencing Factorsmentioning
confidence: 99%